"Playing Back the Dissonances": The Battle of Manassas in Context - Ryan Daar (Columbia Undergraduate Research Journal, 2022)
Before every performance, enslaved pianist-composer Thomas “Blind Tom” Wiggins would introduce his Battle of Manassas as a programmatic depiction of the titular Confederate victory. With sharply juxtaposed fragments of Northern and Southern tunes, along with drum motifs, bugle calls, “The Star-Spangled Banner,” and vocal enactments of trains and whistles—all continually interrupted by sudden “cannon fire” in the left hand—Wiggins would finish the piece shouting “Retreat! Retreat! Retreat!” at the top of his lungs before leaving two irreverent slams of the keys to reverberate throughout the hall. Famous for his lifelong ability to perfectly imitate any music, noise, or speech he heard, Wiggins amazed his audiences for decades claiming to represent Manassas’s events exactly as he heard them described to him. But over 150 years after its premiere, scholars have tended to detect a sense of irony, if not total subversion, in the enslaved pianist’s chaotic Confederate homage. My research considers recent interpretations of the piece with an eye toward its compositional circumstances, including its supposed timeline, its printed foreword’s odd reversal of an anthem’s Southern affiliation, and its likely response to a contemporaneous battle piece by Northern pianist-composer Louis Moreau Gottschalk.